The Correlation Between Parent Communication and Knowledge Regarding Sexual Behavior in Adolescents - Azzizah, Deviana Nur; Imansari, Bhekti; Apriani, Nuni; Syabariyah, Sitti (The Indonesian Institute of Science and Technology Research, 2024)
Premarital sexual behavior in adolescents tends to increase. This is caused by several factors, one of which is low knowledge about sexual behavior. Knowledge in adolescents is one of the duties of parents. Therefore, communication between parents and adolescents is important. This study aims to determine the relationship between parental communication and knowledge about sexual behavior in adolescents. The research method used is a descriptive correlation with a cross-sectional approach. The population of this study is adolescents aged 12-15 years living at home with their parents. The number of samples was 114 The research instrument used a knowledge questionnaire and FARBCS. The data analysis used was univariate and bivariate analysis with bivariate analysis using the Spearman rank test. The results showed that 51.8% of the 114 respondents had adequate knowledge and 88.6% of respondents had open communication. The results of the correlation test showed a p-value of 0.884. The conclusion from this study is that there is no relationship between parental communication and knowledge about sexual behavior in adolescents. It is hoped that future researchers will examine the factors that influence knowledge about sexual behavior.